Catalytic asphaltene upgrading under methane environment: Solvent effect and its interaction with oil components. (1st May 2021) - Xu, Hao; Li, Zhaofei; Li, Yimeng; Song, Hua
Graphical abstract: Catalytic asphaltene upgrading were carried out using typical oil components as solvents under methane environment. Highlights: Catalytic asphaltene upgrading was carried out under CH4 using typical solvents. Solvent effect for better asphaltene upgrading performances was observed. Paraffinic solvents lead to higher light fraction yield and better sulfur reduction. Chemical reactions between aromatic solvents and asphaltenes are limited. Asphaltenes also influence the reactions of solvent molecules. Abstract: Asphaltenes are widely existing in crude oils, which are generally the heaviest and most intractable components with low value. However, it has been proved in our previous study that catalytic heavy oil upgrading process under methane environment can effectively convert asphaltenes into light fractions, leading to remarkable improvement of oil qualities such as decreased TAN, sulfur content and higher yield of light fractions. In this work, asphaltenes were extracted and upgraded under methane environment using several typical paraffinic and aromatic oil components as the solvents. It was found that the presence of solvent facilitates the mixing of catalyst and asphaltenes, reducing coke formation and enhancing the yields of light products. Specifically, paraffins such as heptane and eicosane lead to slightly decreased asphaltene conversion but much higher light fraction yield, which can be attributed to the formation of small hydrocarbon radicals through cracking of the paraffinic chain. Although aromatic solvents such as toluene and 1-methylnaphthalene have little interaction with asphaltenes in terms of chemical reactions during the upgrading process, heavier aromatic components such as 1-methylnaphthalene demonstrate noticeable solvent effect, which successfully prevent the excessive polymerization of asphaltenes towards coke formation by improving the dispersion of asphaltenes. It is suggested that this solvent effect is closely related to phase behavior, which is determined by whether the solvent remains in liquid phase under given reaction conditions. On the other side, the presence of asphaltenes generally lowers the conversions of methane and solvents by partially covering the catalytic surface. For paraffinic solvents, asphaltenes also reduce the selectivity of converted solvent molecules towards aromatics by blocking internal pores of catalysts. In summary, the interaction between solvent molecules and asphaltenes is essential for successful asphaltene conversion to desirable products in heavy oil upgrading processes.